Validity of Questions in The Application of STEM Projects to Increase Learning Outcomes and Students' Learning Motivation on Environmental Change and Preservation Materials - Salwa Afniola; Wiwit Artika; Hafnati Rahmatan; Cut Nurmaliah; Abdullah Abdullah (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
AbstractValidation of learning outcomes test kits is something that must be done to comply with ISO 9001-2000 quality management which requires the instrument to meet quality rules for the process of measuring competence on student learning achievement. This study aims to determine the level of validation of learning outcomes test items used in the implementation of the research exercise learning approach and to analyze the quality of the learning outcomes test. Purposive sampling is the technique used in this study with a sample of 30 people. The process of collecting data is carried out by giving tests to students in the form of multiple choice as many as 40 questions. Then the data were analyzed quantitatively. Based on the results of the study, it is known that each item has a different validity value. The average value of item validity is 0.258 and among the 40 questions, there are 10 items that cannot be used and 30 items that can be used. Keywords: validation, learning outcomes, question. AbstrakValidasi perangkat tes hasil belajar merupakan hal yang harus dilakukan agar sesuai dengan manajemen mutu ISO 9001-2000 yang mengharuskan instrumen untuk memenuhi kaidah-kaidah berkualitas untuk proses pengukuran kompetensi pada prestasi belajar peserta didik. Penelitian ini bertujuan untuk mengetahui tingkat validasi butir soal tes hasil belajar yang digunakan pada pelaksaan pendekatan pembelajaran latihan penelitian serta untuk menganalisis kualitas tes hasil belajar tersebut. Purposive sampling merupakan teknik yang digunakan pada penelitian ini dengan sampel sejumlah 30 orang. Proses dikumpulkannya data dilakukan dengan pemberian tes kepada peserta didik berbentuk pilihan ganda sebanyak 40 butir soal. Lalu data dianalisis secara kuantitatif. Berdasarkan hasil penelitian diketahui bahwa masing-masing butir soal memiliki nilai validitas berbeda. Nilai rata-rata validitas butir soal adalah 0,258 dan diantara 40 soal, terdapat 10 butir soal yang tidak dapat digunakan dan 30 butir soal yang bisa digunakan.Kata Kunci: validasi, hasil belajar, soal